Neuroblastoma - Hayat, M.A (Pediatric Cancer, Diagnosis, Therapy, and Prognosis, 2012)
Introduction of new technologies and their applications to neuroblastoma diagnosis, treatment, and therapy assessment are explained. Role of molecular ghenetics in diagnosis and therapy for neuroblastoma patients is detailed. Molecular detection of minimal residual neuroblastoma is described. Magnetic resonance imaging and  spectroscopy are detailed for diagnosing this solid, extracranial cancer. Targets for therapeutic intervention in neuroblastoma are identified, including targeting multidrug resistance in this cancer. Ornithine decarboxylase and polyamines are novel targets for therapeutic intervention. The effectiveness of chemotherapy with oral irinotecan and temozolomide is explained. The role of transcription factors (GATA) in neuroblastoma pregression is  also included.